A educação ambiental nos livros didáticos de ciências da educação de jovens e adultos - Fonseca, Débora Motta da (2019)
We are going through an environmental crisis that is getting worse and faster due to human relations with nature in many aspects. Therefore, economic and cultural relations between man and nature and between men need to be reviewed. There is a tendency to emphasize Environmental Education (EE) only in the early years of elementary school, assuming that they are individuals in formation. And, should not students of the Youth and Adult Education (YAE) modality participate in this process? This research aimed at the Modern YAE Collection, for the 2nd Stage of YAE (final years of Elementary School), whose general objective was to analyze the approaches of EE that are present in the Science content of the referred Collection, chosen in the National Program of Textbook for YAE, 2014, in the state education network of Goiás. Thus, with a qualitative approach, and using the method of content analysis, the present work analyzed textbooks, from the categories of Sauvé currents. (2005b). After the separation of data by categories, inferential interpretation was performed, seeking in the manifest content, the latent content of the documents. The presence of the environmental issue was verified along all volumes from several units, but superficially, with little criticism for a behavioral and reflexive change in the students. And so, we discovered that despite the various possible ways to practice EE, the Collection presents restricted content and activities, with a traditional approach to EE.